The Effectiveness of Inquiry-Based Science Web-Module on the Students’ Thinking Skills and Positive Attitudes Towards Science - Ray Cinthya Habellia; Suyanta Suyanta (Scientiae Educatia: Jurnal Pendidikan Sains, 2019)
In the 21st century and the industrial revolution era 4.0, students are required to have thinking skills to solve problems around them by utilizing available information. But in Science learning, the material raised is not from the environment around the students. For example, in the material of organism or living things interaction, the ecosystem discussed is outside Indonesia, besides Indonesia has 47 types of ecosystem. One of them is Dieng. Less contextual Science material causes poor of students positive attitude towards Science. Thus, the purpose of this study is to identify the effect of using the Science module web on thinking skills and positive attitude towards Science. This study was a quasi-experimental study with class 7C and class 7D in SMP N 1 Wonosobo as subjects. Data collection technique used question and questionnaire. Data were processed using the Kruskal Wallis test, and it was found that the effect was largely using the effect size. The result of the study shows that there are differences in thinking skill and positive attitude towards Science between the experimental and control classes. The web module Science has a significant effect on thinking skill with effect size large of 0,9 and moderate effect on positive attitude towards Science with an effect size of 0,7.